MELACAK MAQHASHID NIKAH DALAM PERSETUJUAN CALON MEMPELAI WANITA DALAM PERKAWINAN DI INDONESIA - Moh. Dliya’ul Chaq (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2019)
Abstract : In the science of fiqh it is explained that asking permission for a woman's consent in the marriage to the girl is not a widow, because the widow knows more about herself and is experienced in navigating domestic life, permission of a virgin (girl) only by silence because girls feel ashamed to be frank Meanwhile, approval of a widow with clear words from her, if a girl is silent or smiling and does not cry or cry sadly, then it is a sign of her agreement to get married. A woman's approval will be directly related to the feeling of a girl who will accompany her husband for life, he will undergo and will feel happiness and peace in his household, so asking for the approval of a girl and widow in marriage is highly recommended, because the purpose of marriage (Maqhashid al-nikah) is to form a family that sakinah mawaddah warahamah.